On the institutional (dis)organisation of semiotics as a discipline - Herrera, Eduardo Chávez (Estudos Semióticos, 2023)
Semiotics, as the field dealing with the production of meaning-making mechanisms, was supposed to be a holistic project. Semioticians in the 20th century were concerned about providing semiotics an epistemological identity. For instance, semiotics was aimed at following a meta-role (Greimas, 1976) as ‘a metadiscipline of all academic disciplines’ (Posner, 2003, p. 2366). In fact, Sebeok (1976) deemed semiotics as a ‘doctrine of signs’, refusing to call it a science or a theory. Despite this sophisticated terminology, semiotics remained poorly organised in the national academic systems. This lack of organisation in the academic institutions did not allow semiotics to show this allegedly federative role of general knowledge. Instead, semiotics ended up receiving different designations such as ‘esoteric knowledge’, ‘cabalistic language’, ‘formalistic paranoia’, and so forth. This paper delves into the institutional disorganisation of semiotics by addressing two main aspects. Firstly, the lack of interest by early semioticians to accurately organise their field in the institutions, and secondly, how this treatment, as a meta-field, thwarted its aspirations to be considered as a fully-fledged discipline. Thirdly, I engage in a current discussion (Parra, 2020) in semiotics that questions how semiotics has favoured applied approaches to the production of meaning.